Influence of Cover Crop Mixtures on Soil Physical and Chemical Properties in Maize Production - Michael, G. C.; Dania, S. O.; Gisilanbe , S. A. (Journal of the Bangladesh Agricultural University, 2024)
Land use intensification, soil degradation and weed infestation limit the productivity of nutrient-sensitive crop such as maize. Mixed cover cropping has potentials to address these challenges in an ecological friendly manner. Field experiments were conducted between 2007 and 2009 at the Taraba State College of Agriculture Teaching Farm, Jalingo, Nigeria to evaluate the effects of a leguminous cover crop, Akidi (A), Vigna unquiculata sub-sp sequipedalis) and two non-leguminous cover crops (Melon M) and Sweet potato (S) planted in all possible combinations at three planting densities used primarily for weed control on soil conservation and maize production. Treatments include 20,000(1), 30,000(2) and 40,000(3) stands ha-1 of AM (AM1, AM2, AM3), AS (AS1, AS2, AS3), MS (MS1, MS2, MS3) and AMS (AMS1, AMS2, AMS3), weeded (3+6 Weeks After Planting, WAP) (C1) and unweeded (C2) checks replicated three times in a randomized complete block design. Descriptive statistics and Analysis of Variance were used to analyze data and the treatment means were compared using standard error at 5%. A general decrease in calcium (Ca2+), magnesium (Mg2+), potassium (K+), sodium (Na+), pH, exchangeable acidity, available phosphorus (AV-P), % silt and cation exchange capacity (CEC) but a slight increase in organic carbon, total nitrogen (TN), % clay and % fine sand. The AMS treated plots had the highest magnitude of increase in organic carbon (OC). The order of OC improvement was AMS > AM >MS >AS. While increase in TN was AMS > AM >AS >MS. Reduction in AV-P was highest in AM treated plots (90.4%), followed by AS and then MS, while AMS caused the least reduction in AV-P. Fine sand was slightly increased in most treatments. Use of cover crop mixtures for weed management in maize decreased all exchangeable cations, pH, AV-P and CEC, and improved OC, TN and clay content. J Bangladesh Agril Univ 18(4): 901–915, 2020 https://doi.org/10.5455/JBAU.95786